TEACHING ENGLISH BY USING PODCAST: IT’S INFLUENCE ON UNDERGRADUATE STUDENT’S LISTENING COMPREHENSION - Aditya, Maulana Yusuf (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2018)
Listening is the most important skill in learning language, especially English as foreign language. This research was done to know the influence of podcast on undergraduate students’ listening comprehension. Related to the problem, this is a quantitative research. Where the sample is only chose one class as experimental subjects from all third semester of English Department students at STKIP PGRI Bangkalanin academic year 2018/2019 with random sampling technique. To examine hypothesis of the research, the researcher used t-test in which the researcher defined one class as one group pre-test post-test.The finding of the research, it can be concluded that there is an influence ofpodcast on undergraduate students’ listening comprehension. It is shown from the result of this research, that t-value is 23.18 which higher than t-table by the level of significant 0.05 which is 1.72. The suggestion of the researchfor the lecturersthat they can choose the most suitable technique used in listening comprehensiondealing with the level of the students.